2017
DOI: 10.1111/sji.12619
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐3 is Persistently Increased in Early Rheumatoid Arthritis (RA) and Associates with Anti‐CCP Seropositivity and MRI Bone Lesions, While Early Fibrosis Markers Correlate with Disease Activity

Abstract: Galectin-3 has been suggested as a pro-inflammatory mediator in animal arthritis and rheumatoid arthritis (RA). We aimed to study the serum level of galectin-3 in patients with newly diagnosed RA and associations with disease profile, Magnetic resonance imaging (MRI) findings and seromarkers of synovial matrix inflammation. One hundred and sixty DMARD naïve patients newly diagnosed with RA were included (CIMESTRA study). Clinical, serological and imaging data were recorded before treatment and at 6 weeks, 3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
(45 reference statements)
1
17
0
3
Order By: Relevance
“…Heart disease acute heart failure plasma level combination with natriuretic peptide [62] acute heart failure plasma level promising prognostic marker [63] chronic heart failure plasma level useful in HF patients with preserved LVEF [64] chronic heart failure myocardial and plasma level not associated with histology [65] acute myocardial infarction serum level no definite relationship with ventricular remodeling [66] Nervous system diseases myelin degeneration tissues activation of the phagocytosis of degenerated myelin [42] intracerebral hemorrhage plasma level prognostic predictor [67] subarachnoid hemorrhage plasma level prognostic predictor [68] global brain ischemia cerebrospinal fluid prognostic marker and inflammatory mediator [69] Renal disease CKD plasma level associated with progression of CKD [25] SLE nephritis serum and biopsy specimens associated with SLE patients, particularly in SLE nephritis [70] Liver disease liver fibrosis serum Gal-3 related binding protein assessing liver fibrosis [71] Connective tissue diseases rheumatoid arthritis serum level increased in early rheumatoid arthritis [72] SLE serum anti-Gal-3 antibody a key role in SLE skin lesions [73] systemic sclerosis serum level predictor of mortality [74] Neoplasms colorectal cancer serum and tissues related to tumor progression [52] breast cancer human cell lines important factor for treatment [75] non-small cell lung cancer tumor expression promotion of invasion and metastasis [76] lung and prostate cancers tumor expression therapeutic target of tumor immunity [77] cervical cancer tumor expression targets of multifunctional cancer treatment [78] thyroid cancer tumor expression diagnostic marker [79]…”
Section: Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart disease acute heart failure plasma level combination with natriuretic peptide [62] acute heart failure plasma level promising prognostic marker [63] chronic heart failure plasma level useful in HF patients with preserved LVEF [64] chronic heart failure myocardial and plasma level not associated with histology [65] acute myocardial infarction serum level no definite relationship with ventricular remodeling [66] Nervous system diseases myelin degeneration tissues activation of the phagocytosis of degenerated myelin [42] intracerebral hemorrhage plasma level prognostic predictor [67] subarachnoid hemorrhage plasma level prognostic predictor [68] global brain ischemia cerebrospinal fluid prognostic marker and inflammatory mediator [69] Renal disease CKD plasma level associated with progression of CKD [25] SLE nephritis serum and biopsy specimens associated with SLE patients, particularly in SLE nephritis [70] Liver disease liver fibrosis serum Gal-3 related binding protein assessing liver fibrosis [71] Connective tissue diseases rheumatoid arthritis serum level increased in early rheumatoid arthritis [72] SLE serum anti-Gal-3 antibody a key role in SLE skin lesions [73] systemic sclerosis serum level predictor of mortality [74] Neoplasms colorectal cancer serum and tissues related to tumor progression [52] breast cancer human cell lines important factor for treatment [75] non-small cell lung cancer tumor expression promotion of invasion and metastasis [76] lung and prostate cancers tumor expression therapeutic target of tumor immunity [77] cervical cancer tumor expression targets of multifunctional cancer treatment [78] thyroid cancer tumor expression diagnostic marker [79]…”
Section: Diseasesmentioning
confidence: 99%
“…Gal-3 has been reported to be expressed and secreted by inflamed synovium in patients of rheumatoid arthritis and osteoarthritis. Issa and colleagues reported that Gal-3 serum levels was persistently increased in early rheumatoid arthritis, and a positive correlation was observed between Gal-3 serum levels and some associated pathophysiology, such as autoimmunity, smoking, and joint destruction [72,120]. In experimental animal models for osteoarthritis, Gal-3 has been demonstrated to induce joint swelling and osteoarthritis-like lesions after intra-articular injection [119].…”
Section: Rheumatoid Arthritis and Osteoarthritismentioning
confidence: 99%
“…Recent studies suggest that galectins play important roles in the pathogenesis of RA [7]. It was demonstrated that galectin-3 is increased in early RA and associated with anti-CCP seropositivity and MRI bone erosion scores in patients with RA [8]. These findings suggest that galectin family plays an important role in the disease development of RA, through their interactions with innate or adaptive immunity.…”
Section: Introductionmentioning
confidence: 96%
“…Существует мнение о возможности использования данного белка в качестве маркера эффективности лечения РА [21]. Описано повышение уровня галектина-3 при наличии положительного титра антител к циклическому цитруллиновому пептидуI: 4,2 (3,6;6,1) против 3,8 (3,0; 4,8) мкг / мл (р<0,01) в группе контроля [22]. Следовательно, определение уровня галектина-3 в группе пациентов, страдающих ХСН на фоне РА, может играть важную диагностическую роль, так как повышенный уровень галектина-3 при нормальных значениях натрийуретических пептидов может указывать на диастолическую дисфункцию миокарда.…”
Section: галектин-3unclassified